2008
DOI: 10.1186/1471-2334-8-32
|View full text |Cite
|
Sign up to set email alerts
|

Basis for treatment of tuberculosis among HIV-infected patients in Tanzania: the role of chest x-ray and sputum culture

Abstract: Background: Active tuberculosis (TB) is common among HIV-infected persons living in tuberculosis endemic countries, and screening for tuberculosis (TB) is recommended routinely. We sought to determine the role of chest x-ray and sputum culture in the decision to treat for presumptive TB using active case finding in a large cohort of HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 25 publications
5
15
0
Order By: Relevance
“…The tuberculous abscess is rare in non-HIV infections, accounting for only 4e8%, but the ratio could reach 20% in HIV infections. In this study, 4 cases of abscess lesions with ring-enhancement were documented, which echoed to the previous report [10]. In the cases with AIDS and concurrent brain infections, the toxoplasma encephalopathy showed an incidence just below that of the HIV encephalopathy incidence, which proved the major opportunistic infection of the nervous system in AIDS patients [11], especially those with CD4 þ T < 100 cells/mm 3 .…”
Section: Discussionsupporting
confidence: 84%
“…The tuberculous abscess is rare in non-HIV infections, accounting for only 4e8%, but the ratio could reach 20% in HIV infections. In this study, 4 cases of abscess lesions with ring-enhancement were documented, which echoed to the previous report [10]. In the cases with AIDS and concurrent brain infections, the toxoplasma encephalopathy showed an incidence just below that of the HIV encephalopathy incidence, which proved the major opportunistic infection of the nervous system in AIDS patients [11], especially those with CD4 þ T < 100 cells/mm 3 .…”
Section: Discussionsupporting
confidence: 84%
“…A recent Ugandan study in HIV-infected patients starting ART revealed a high sensitivity and negative predictive value for the presence of several baseline factors (one of cough ≥ 3 weeks, fever ≥ 4 weeks, lymphadenopathy, or reduced body mass index) [21]; this study population had a much lower TB prevalence and included physical examination data that the current study did not. In the current study, the most sensitive strategies included a baseline CXR; the addition of baseline CXR to symptom screening and AFB smear has shown improved sensitivity of TB diagnosis in other African settings with high HIV prevalence [22, 23]. However, the most sensitive combinations of screening tools had very low specificity (15%), such that relying solely on tests available at baseline would lead to many patients being treated for TB who do not have the disease, incurring unnecessary toxicity and costs.…”
Section: Discussionmentioning
confidence: 99%
“…Such patients are more likely to have atypical radiographic findings including non-cavitary pulmonary infiltrates sparing the lung apices 85 86. One consequence of the lower frequency of pulmonary cavitation in HIV infection is that patients are more likely to have smear-negative pulmonary disease, although this is also the case for those with extrapulmonary TB 87 88. The value of tuberculin skin testing (TST) in patients with HIV is limited due to high false negative rates and in advanced immunosuppression a negative test does not exclude a diagnosis of TB 89…”
Section: Clinical Manifestationsmentioning
confidence: 99%